FAKTOR - FAKTOR YANG MEMPENGARUHI KECEMASAN SEBELUM DILAKUKAN TINDAKAN SECTIO CAESAREA DI RSIA ANUGERAH KUBURAYA PONTIANAK KALIMANTAN BARAT - yusnita riki (NHM PRESS, 2021)
The general goal to be achieved in this study is to determine the factors that influence anxiety in clients before an unplanned Sectio Caesarea is performed at Anugerah Kuburaya RSIA. The research method is a qualitative descriptive research, the data that has been obtained is then processed using the stages, Editing, Coding and Processing. The result of this research is that there is an influence but not significant between the predisposing factor, and the precipitation factor on the client's anxiety before the unplanned Sectio caesarea at RSIA Anugerah Kuburaya. For researchers who will conduct similar research in the future, it is expected to take a more specific title, for example, it can be distinguished between anxiety in clients who will perform unplanned Sectio Caesarea surgery with anxiety on clients who will perform planned Sectio Caesarea.